Preparation and anticancer evaluation of potassium-N-(P-anisole)-a-(O-Xanthetovanillin)-nitrone - Nohad A. Al-Omari (University of Mosul, 2006)
The new compound, "Potassium -N-(P-methoxy phenyl)-a-(O-Xanthetovanillin)- nitrone was prepared and characterized by elemental analysis, IR and molar conductance. The anticancer activity of it had been achieved by the assistance of the National Cancer Institute (NCI) USA. Here we show that vanillin (3-methoxy-4-hydroxybenzaldehyde); a naturally occurring food component and an acknowledged antimutagen, anticlastrogen and anticarcinogen-is an inhibitor of the activity of nine types of cancer cells specially the Colon, CNS and Renal cancer